Identification of potential bioactive compounds of Passiflora edulis leaf extract against colon adenocarcinoma cells (2023)
ABSTRACT: Plant bioactive compounds such as flavonoids and triterpenes can affect lipid metabolism. Here, we report the cytotoxic and lipid-lowering activities of the ethanolic extract of P. edulis leaves on human colon adenocarcinoma SW480 cells, also the molecular interactions of bioactive compounds present in P. edulis extract on ACC and HMGCR enzymes. The extract reduced cell viability and decreased intracellular triglyceride content by up to 35% and 28% at 24 and 48 h, respectively; whereas the effect was evident on cholesterol only at 24 h. In-silico analysis revealed that luteolin, chlorogenic acid, moupinamide, isoorientin, glucosyl passionflower, cyclopasifloic acid E and saponarin had optimal molecular coupling on Acetyl-CoA Carboxylase 1 and 2 as well as 3 hydroxy-3-methyl-glutaryl-CoA reductase, with possible inhibitory effects. These results show the ability of ethanolic extract to reduce intracellular levels of cholesterol and triglycerides in SW480 cells, which attracts attention for the treatment of colorectal cancer.